Higher levels of harsh parenting during the COVID-19 lockdown in the Netherlands - Sari, Novika Purnama (Child maltreatment, 2022)
Previous studies on the impact of COVID-19 indicate that pandemic-related distress increases risks for child maltreatment, although data on the scope of this problem are still scarce. Here, we assessed whether parents with toddlers (n = 206) more often used harsh discipline during the lockdown in the Netherlands compared to a matched parent sample collected prior to the pandemic (n = 1,030). Parents were matched on background characteristics using propensity score matching. We found that harsh parenting levels were significantly elevated compared to pre-pandemic levels. Harsh parenting behaviors with a low prevalence before COVID-19 increased most strongly: shaking, calling names, and calling the child stupid. These results suggest that parental tolerance for children’s disobedience is lower under the adverse circumstances of COVID-19 and, as a result, abusive parenting responses are more difficult to inhibit. Thus, a lockdown seems to increase risks for child maltreatment, underscoring the need for effective support strategies for at-risk families.